Faktor yang Berkontribusi terhadap Stroke Serta Strategi dan Penanganan Medis dan Rehabilitasi - Pui, Manuela Monalisa Lindalva; Priyanto Priyanto (Pusat riset dan Inovasi Nasional, 2026)
Stroke is one of the non-communicable diseases that is the leading cause of disability and death in the world. Clinical factors such as hypertension, diabetes mellitus, body mass index (BMI), and unhealthy lifestyle are known to contribute to the incidence of stroke. Oe-Cusse Referral Hospital serves as the main referral center in the treatment of stroke cases, but data on contributing clinical factors and medical treatment and rehabilitation strategies are still limited. This study aims to analyze the clinical factors that contribute to the incidence of stroke and describe medical treatment and rehabilitation strategies in stroke patients at Oe-Cusse Referral Hospital.This study is a quantitative study with a cross-sectional observational design. The research sample amounted to 50 stroke patients who were treated in the January-November 2025 period, selected using purposive sampling techniques. Data were collected through medical records and questionnaires related to medical treatment and rehabilitation. Data analysis was carried out using the SPSS program, including descriptive analysis and logistic regression to see the relationship between clinical factors (hypertension, diabetes mellitus, lifestyle, BMI, and other factors) and stroke incidence. The results of the descriptive analysis showed that the average age of stroke patients was 56.2 ± 9.8 years, with an age range of 39–78 years. The average BMI of the patient was 27.5 ± 3.1 kg/m² which indicates a tendency to be overweight. The average systolic blood pressure of the patient was 150 ± 18 mmHg, indicating the predominance of hypertension in stroke patients. The average length of rehabilitation lasted 6.3 ± 1.8 weeks. Logistic regression analysis showed a significant relationship between clinical factors, especially hypertension, BMI, and diabetes mellitus, and stroke incidence. Clinical factors such as hypertension, high BMI, and diabetes mellitus contribute significantly to the incidence of stroke at Oe-Cusse Referral Hospital.